Effect of Intensity Reading News About the Economic Policy Jokowi in Viva.co.id and Image Jokowi to Public Trust Level Jokowi Regarding performance in the Economy - Ahmad Khairul Nuzuli (Interaksi Online, 2016)
As an online media mass media also performs the function of social control, as mandated by Law No. 40 of 1999 on the Press. Social control is realized through reporting on the performance of the government portraits. Jokowi as a government figure who holds the office of President of the Republic of Indonesia, can not be separated from the media spotlight, including Viva.co.id one jokowi economic policy. Intensity of the public to read the news about economic policy Jokowi potentially affect their trust level regarding the performance Jokowi in economics. In addition jokowi image can also affect the level of public confidence. This study aims to determine determine the effect intensity of reading news about economic policy in Viva.co.id and Image Jokowi to Public Trust Level Jokowi Regarding performance in the Economy . The rationale used is the Cognitive Effects of Mass Media Theory and Expectancy Value Theory. This type of research is explanatory research. This study using the technique of Non-probability sampling with accidental sampling method to determine the sample. The total sample of 50 respondents who met the criteria Viva.co.id readers aged over 17 years in the city of Semarang. Analysis of the data used is simplistic linear regression SPSS. The first hypothesis test results show that the variable intensity of reading news about economic policy Jokowi in Viva.co.id (X1) does not affect the level of public trust the performance of Jokowi in the economy (Y) and showed no significant results, with the result Sig / significance worth 0257 or probability greater than 0.05. The second hypothesis test showed Jokowi image variables (X2) and highly significant positive effect on the level of public trust in the performance of Jokowi in the economy (Y) with the Sig / significance worth 0.000 or probability of less than 0.05 and contributions effect as much as 64%. this indicates a relatively high contribution. Advice can be given is the President Jokowi must be to maintain and enhance the good image to the public. People who have had positive experiences with the performance of Jokowi will generate a positive perception and image also against Jokowi.